1989
DOI: 10.1071/sr9890161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil moisture regime on the respiration response of soils subjected to osmotic stress

Abstract: The influence of the soil moisture regime on the tolerance of the soil micro-organisms to increased osmotic stress was examined by laboratory tests with a range of New Zealand soils. Soils from various climatic regions (moist, intermediate and dry) were amended with glucose-NaCl solutions, incubated for 0.5 h, and the respiration rate over the following 2 h was used as a measure of the response of the microbial biomass to the changed osmotic potential. Osmotic potentials were varied between -4 and -80 bar by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These apparently negative relationships may be due to enhanced microbivory in conditions of high soil moisture (Flanagan & van Cleve, 1977;Clarholm & Rosswall, 1980) or death of plant roots during extended dry periods which may stimulate growth of drought-tolerant fungi (Ross, Orchard & Rhoades, 1 9 8 4~;Raghubanshi, 1991). The results of a similar study (Sparling, West & Reynolds, 1989) did not conform to this, however. Kieft, Soroker & Firestone (1987) proposed that rewetting dry soils may exert negative effects on the microbial biomass through osmotic stress.…”
Section: (6) Soil Moisture and Temperaturementioning
confidence: 74%
See 1 more Smart Citation
“…These apparently negative relationships may be due to enhanced microbivory in conditions of high soil moisture (Flanagan & van Cleve, 1977;Clarholm & Rosswall, 1980) or death of plant roots during extended dry periods which may stimulate growth of drought-tolerant fungi (Ross, Orchard & Rhoades, 1 9 8 4~;Raghubanshi, 1991). The results of a similar study (Sparling, West & Reynolds, 1989) did not conform to this, however. Kieft, Soroker & Firestone (1987) proposed that rewetting dry soils may exert negative effects on the microbial biomass through osmotic stress.…”
Section: (6) Soil Moisture and Temperaturementioning
confidence: 74%
“…This was based on an experiment which demonstrated that mineralization of microbial carbon induced by soil moisture potential increases exceeded the potential respiration attributable to microbial death due to prior desiccation. The results of a similar study (Sparling, West & Reynolds, 1989) did not conform to this, however. Although the microbial biomass is also known to be negatively influenced by osmotic effects caused by salinity (Malik & Azam, 1980), the influence of osmotic potential on the microbial biomass, especially in relation to soil moisture content, is poorly understood.…”
Section: ( a ) Soil Texture And Structurementioning
confidence: 75%
“…Many studies of the relationship of soil respiration with soil temperature or soil water content alone have been reported (Sparling et al 1989;Howard and Howard 1993;Lloyd and Taylor 1994;Davidson et al 1998;Qi and Xu 2001;Schwendenmann et al 2003). In fact, the empirical relationships between soil respiration and soil temperature or moisture may confound the effects of each other, since the factors co-vary across seasons (Howard and Howard 1993;Li et al 2008).…”
Section: Soil Respirationmentioning
confidence: 97%
“…The jars were incubated at 4°C overnight for equilibration before placing them at 2 different incubation temperatures (23°C and 4°C). The head-space gas was sampled (1 mL) via the septum and the CO 2 concentration measured using an infra-red gas analyser (Sparling et al, 1989). Measurements of respired CO 2 were first taken at day 5, and then every 2 days for 2 weeks and finally once a week up to the end of the incubation time (42 days).…”
Section: Soil Respirationmentioning
confidence: 99%